Analysis of Operative Techniques of Fractures of the First Metacarpal Base. Issue 5 (May 2018) - Fischborn, Till; Beckenbauer, Dominik; Held, Manuel; Daigeler, Adrien; Medved, Fabian
Abstract : Introduction: Over time, the operative treatment of extra-articular and intra-articular fractures of the first metacarpal base has gained significant importance, and at present, there are many operative strategies available because of the different osteosynthesis procedures in practice today. Purpose: In this retrospective cohort study, we analyze the possible differences between 2 distinguished operative osteosynthesis techniques, in terms of patient outcome, operation time, duration of radiation exposure, and postoperative radiographic results. Methods: Fifty-two patients operated on for first metacarpal extra-articular or intra-articular base fracture were investigated retrospectively by means of records. After reduction, osteosynthesis was performed on 34 patients with K-wires (group I), and on 18 patients with plates and/or screws (group II). Of the 52 patients, 19 were available for a prospective follow-up examination. Results: After analyzing the operation time, a significant difference between the 2 operative techniques for epibasal and Bennett fractures ( P = 0.0089 and P = 0.02) was recorded. Furthermore, for the time of radiation exposure, no significant difference could be detected. Also, no statistical difference was found between the 2 analyzed groups in terms of patient outcomes and postoperative radiographic results. Conclusions: The determined data of the operated extra-articular and intra-articular first metacarpal base fractures revealed approximately equal results for patient outcome, postoperative x-ray results, and time of radiation exposure during the operation. After analyzing the operation time of epibasal and Bennett fractures, we can recommend that the K-wire fixation is superior to the plate and/or screw osteosynthesis as a treatment, because of the associated benefits of keeping costs low without harming the patient in the long term.